Textual kidnapping revisited: the case of plagarism in literary translation - Turell, M. Teresa (International Journal of Speech, Language and the Law, 2004)
Linguistic analysis of plagiarized literary translation for forensic purposes has not been addressed before. What makes this type of plagiarism different from others, and thus more difficult to detect, has to do with the nature of translation itself:|on the one hand, all translations will tend to reflect the author’s original form and content, and in so doing resemble the original work, and on the other, the more faithful|they are to the original piece of work, the more difficult it is to detect their originality. The case of plagiarism under consideration had already been decided (Judgment 1268 of the Supreme Court, Madrid, 29 December 1993) when this study was undertaken. The data for analysis include four translations into Spanish of Shakespeare’s Julius Caesar: those of Astrana MarÃn 1961, Valverde 1968, Pujante 1987 (the plagiarized|translation), and Vázquez Montalbán 1988 (the disputed translation). By presenting evidence deriving from the application of CopyCatch to the four translation|texts, it is argued that such evidence can better assist the analyst and, in this case, the prosecution, in cases of plagiarism between translations.